The Police Service as a Guardian of Public Security and Public Order in Contemporary Poland - Fehler, Włodzimierz (Przegląd Strategiczny, 2013)
Public safety and public order are fundamental elements of the sphere of internal safety of the State. The presented article, having shown the essence of and interrelationships between public safety and public order, deals with the issues of the role and tasks of the Police service as one of the most important guardians of those aspects of Poland’s internal safety. The principal themes of the study focus on such issues as: the statutory tasks, organisational structures, police authorities, personnel and material assets. Apart from indicating general statutory tasks, the articles shows them also in a broader perspective, in the context of the tasks performed at particular organisational levels: the central level represented by the National Headquarters, the regional level managed by Provincial headquarters and the local level for which county headquarters and the subordinate police stations and posts are responsible. In showing the Police force as one of the most important entities ensuring public safety and public order, the special tools which Police has at its disposal, namely compact crime prevention squads and anti-terrorist units, have been described as well. Finally, the articles presents the characteristics of the personnel assets (the number of personnel, description of the length of service among particular corps) and material assets (number of vehicles, basic armament, police air-force dislocation and aircraft).